2002
DOI: 10.1108/09590550210415248
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between trust, commitment and relationship quality

Abstract: Attempts to examine the concepts of trust and commitment, on two levels of retail relationships: the salesperson level as well as the store level, and test their impact on relationship quality. Based on a review of the literature, a conceptual model has been developed that links trust and commitment to relationship quality. A number of research hypotheses have been formulated to examine the relationships proposed. The paper presents the model developed and discusses some empirical findings from a survey of 1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
294
3
17

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(323 citation statements)
references
References 82 publications
9
294
3
17
Order By: Relevance
“…Current arena is the period of accelerated and unpredictable evolutions and companies confront with the most difficult and unprecedented competition conditions due to existence of such factors like uncertain boundaries among markets ‚ more fragmentation of markets ‚ shortened product consumption period‚ accelerated variation of customers purchasing paradigms and customers being more expert [Wong and Shohal 2002].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current arena is the period of accelerated and unpredictable evolutions and companies confront with the most difficult and unprecedented competition conditions due to existence of such factors like uncertain boundaries among markets ‚ more fragmentation of markets ‚ shortened product consumption period‚ accelerated variation of customers purchasing paradigms and customers being more expert [Wong and Shohal 2002].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of researchers have investigated these dimensions as part of a higher order construct, relationship quality, in B2B as well as business to consumer (B2C) situations (Dorsch et al, 1998;Hennig-Thurau and Klee, 1997;Hewett et al, 2002;Roberts et al, 2003;Shamdasani and Balakrishnan, 2000;Svensson et al, 2009;Walter et al, 2003;Wong and Sohal, 2002). In a number of studies, trust and commitment are presented as independent concepts (Hewett et al, 2002;Morgan and Hunt, 1994;Ruyter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that trust leads to commitment (Becker, 1960;Axelrod, 1984;Morgan & Hunt, 1994;Wetzels et al, 1998;Garbarino & Johnson, 1999;Varamä ki, 2001;Ylimaz & Hunt, 2001;Ekelund, 2002;Rodriguez & Wilson, 2002;Wong & Sohal, 2002;Mukherjee & Nath, 2003). We propose that trust can be reinforced through interpersonal commitment (Morgan & Hunt, 1994) and ultimately enhance interorganizational commitment (Mavondo & Rodrigo, 2001).…”
Section: Trust (Tru)mentioning
confidence: 99%
“…To minimize these risks, firms in successful networks share resources and operations with others they can trust. Trust initially leads to greater interpersonal commitments (Becker, 1960;Axelrod, 1984;Morgan & Hunt, 1994;Wetzels et al, 1998;Garbarino & Johnson, 1999;Varamä ki, 2001;Ylimaz & Hunt, 2001;Ekelund, 2002;Rodriguez & Wilson, 2002;Wong & Sohal, 2002;Mukherjee & Nath, 2003) as does reciprocity (Kumar, Scheer & Steenkamp, 1995;Mavondo & Rodrigo, 2001). Moreover, interpersonal commitment ultimately influences interorganizational commitment (Yoon, Baker & Ko, 1994;Mavondo & Rodrigo, 2001).…”
Section: The Modelmentioning
confidence: 99%